2022
DOI: 10.3389/fonc.2022.858148
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implication of Patient Age in H3K27M-Mutant Midline Gliomas

Abstract: IntroductionPediatric and adult H3K27M-mutant midline gliomas have variable clinical presentations, prognoses, and molecular backgrounds. In this study, we integrated data from published studies to investigate the differences between these two groups.MethodsPubMed and Web of Science were searched for potential data. Studies were included if they had available individual participant data on patients age of H3K27M-mutant midline gliomas. For time-to-event analyses, Kaplan-Meier analysis and Cox regression models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
0
12
0
1
Order By: Relevance
“…A systematic review including 43 studies showed more aggressive features, including higher rates of pathologic features of high-grade tumors and a higher Ki-67 proliferation index, occurred in pediatric H3K27M-mutant DMG when compared to adults, which resulted in a worse prognosis in the children subgroup. 25 Moreover, there are differences in the molecular characteristics of H3K27M-mutant DMG between pediatric and adult patients. Several studies demonstrated that ACVR1 mutation frequently occurred in children, whereas FGFR1, neurofibromatosis type 1 (NF1), and ATRX mutations were more common in adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review including 43 studies showed more aggressive features, including higher rates of pathologic features of high-grade tumors and a higher Ki-67 proliferation index, occurred in pediatric H3K27M-mutant DMG when compared to adults, which resulted in a worse prognosis in the children subgroup. 25 Moreover, there are differences in the molecular characteristics of H3K27M-mutant DMG between pediatric and adult patients. Several studies demonstrated that ACVR1 mutation frequently occurred in children, whereas FGFR1, neurofibromatosis type 1 (NF1), and ATRX mutations were more common in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The distinct mechanisms accounting for the different prognosis between children and adults have not been fully explored. A systematic review including 43 studies showed more aggressive features, including higher rates of pathologic features of high‐grade tumors and a higher Ki‐67 proliferation index, occurred in pediatric H3K27M‐mutant DMG when compared to adults, which resulted in a worse prognosis in the children subgroup 25 . Moreover, there are differences in the molecular characteristics of H3K27M‐mutant DMG between pediatric and adult patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82…”
Section: Methodsunclassified
“…DMG H3 K27-altered may also occur in the adult population. 3 We review the features of DMG H3 K27-altered in the adult and pediatric populations and compare their genetic, epidemiological, clinical, radiological, histopathological, treatment, and prognostic characteristics.…”
Section: Idhmentioning
confidence: 99%